IMPROVING STUDENTS SPEAKING SKILLS THROUGH VIDEO AT 12th GRADE OF SMK TECHNOLOGY NATIONAL BEKASI - Delfira, Tasya; Asrori, Ircham (ASIAN PUBLISHER, 2022)
This study aims to improve speaking skills through the video playing method in class students at SMK Technology National Bekasi. The research subjects were 32 students in 12th grade of SMK Technology Bekasi. Data collection methods used are observation and testing. This research uses library research that comes from books and journals. Before collecting data, researchers made an initial examination of 12th graders. Researchers pick students at random one at a time during the study to be asked what they think of the English language. Interview questions are everyday sentence questions that ask about their ability to speak, their difficulty in speaking, and their personal interest in learning English from the media such as videos. The researcher also adopted the method of video-based learning for the treatment. In view of speaking skill, students had to have enough vocabulary in order to produce utterances. Focusing on fluency meant that the students were directed to focus on the flow of utterances freely and smoothly. In conclusion, the majority of them got impressed with contextual; video and started to produce utterances and language expressions. Initially, the majority of them tended to be reluctant and struggled hard to say the words and to produce utterances. However, The implementation of contextual video techniques minimize their hesitation when speaking as a result of vocabulary building and fluency drilling with the material in the contextual video.